Healthcare Worker Mental Health and Wellbeing During COVID-19: Mid-Pandemic Survey Results - Young, Kevin P.; Kolcz, Diana L.; Ferrand, Jennifer; O’Sullivan, David M.; Robinson, Kenneth (Frontiers in Psychology, 2022)
Background: HealthCare Worker (HCW) mental health and wellbeing are uniquely affected by the complexities of COVID-19 due to exposure, isolation, risk and uncertainty. Little if any inquiry has examined the effects on an entire healthcare system, particularly immediately post-surge. Objective: Examine prevalence of psychiatric symptoms and behavioral health difficulties as a healthcare system transitioned out of the first wave. Assess the effects of work role, setting and individual diversity factors on employee distress and coping strategies. Design: IRB approved, unfunded, voluntary survey sent to all employees of a mid-sized healthcare system (N=29,900) between May 15th and June 26th, 2020. Participants: 8,494 employees participated in the survey, representing clinical, support, administrative, and medical staff across hospital, outpatient, residential, and business settings. Measurements: Examination of personal background, work environment/culture, and formal measures, including: Patient Health Questionnaire-9 (PHQ-9), General Anxiety Disorder-7 (GAD-7), Primary Care Post Traumatic Stress Disorder Screen for DSM-5 (PC-PTSD), Alcohol Use Disorders Identification Test (AUDIT-C), and the Insomnia Severity Index (ISI). Results: Almost 1/3 of respondents reported symptoms of clinically significant anxiety (31%); 83% moderate to severe depression; 13% post-traumatic stress disorder; and 51% moderate to severe insomnia. Frontline staff and females endorsed the highest levels of distress, while race and ethnicity had a complex and nuanced interaction with symptoms. Limitation: Lower response rate than ideal, yet yielded important and novel information with no reason to suspect bias. Conclusion: Pandemic stress effects all healthcare employees, though not equally. The effects of work role and environment are intuitive though critical. These data suggest individual diversity factors also play an important role in mental health and wellbeing. All must be considered to optimize functioning.